Effects of Job Level and Participation on Employee Attitudes and Perceptions of Influence - Hrebiniak, Lawrence G. (Academy of Management Journal, 1974)
Job level, in instrumental or technological terms, and perceived deficiency in decision making have differential effects on work related attitudes and perceptions of desired influence or relative power. Implications of the data for task unit structure and process are discussed, along with a recent methodological argument regarding the ?deficiency? of deficiency measures.